2022
DOI: 10.1186/s12912-022-00962-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of educational concerns and satisfaction on baccalaureate nursing students’ distress and quality of life during the Covid-19 pandemic; a cross-sectional study

Abstract: Background High levels of psychological distress and poor overall quality of life (QOL) have been identified among nursing students during the COVID-19 pandemic. The pandemic necessitated improvised reconstructions of educational curriculums and restrictions in clinical placement and training at campuses, possibly reducing educational quality. Objectives We explored whether baccalaureate nursing students’ concerns and satisfaction with the educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In this study, satisfaction with the nursing major was another factor that influenced COVID-19-related psychological distress among senior nursing students. This is in line with results from previous studies, which showed that in the case of Norwegian Baccalaureate nursing students, the higher their satisfaction with their educational curriculum, could then be positively associated with the overall quality of life [27]. More specifically, satisfaction with the nursing major of students is associated with psychological distress during the COVID-19 pandemic and a student's overall quality of life and well-being.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, satisfaction with the nursing major was another factor that influenced COVID-19-related psychological distress among senior nursing students. This is in line with results from previous studies, which showed that in the case of Norwegian Baccalaureate nursing students, the higher their satisfaction with their educational curriculum, could then be positively associated with the overall quality of life [27]. More specifically, satisfaction with the nursing major of students is associated with psychological distress during the COVID-19 pandemic and a student's overall quality of life and well-being.…”
Section: Discussionsupporting
confidence: 91%
“…More precisely, it was noted that nursing student’s general quality of life and well-being during the COVID-19 pandemic were linked to their level of satisfaction with their nursing major. However, professor–student relationships become more challenging for nursing students to navigate in terms of seeking advice and effective communication for career preparation in the post-COVID-19 era [ 22 ]. Furthermore, senior students’ sense of social duty increases with their level of self-efficacy and satisfaction with their nursing major.…”
Section: Discussionmentioning
confidence: 99%
“…Major satisfaction is the result of satisfying one’s needs while studying one’s major while also combining positive thoughts about enjoyment, one’s future, and a career path [ 19 , 20 , 21 , 22 ]. The nursing curriculum included more elective subjects that were directly relevant to the major and was quite stressful because of theory and clinical practice, which lowers major satisfaction [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations